PELAKSANAAN TUPOKSI OMBUDSMAN DALAM PENGAWASAN PELAYANAN PUBLIK OLEH OMBUDSMAN PERWAKILAN RIAU - Hidayat. S "; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to provide an explanation about the main tasks and functions of the Ombudsman of the Republic of Indonesia, especially the Ombudsman Representative Riau. Adapaun frameworks used in describing the execution of the duties of the Ombudsman is to look at the task mastery, ability of cooperation, Completing work on time, granting the right job report results and explain some of the factors that could affect the execution of the duties of the Ombudsman. The data collection was done by direct observation and interviews with informants. The method used in this research is descriptive qualitative method. Based on the results of the study illustrate that in the execution of the duties of Ombudsman Representative Riau has been run in accordance with the applicable provisions in the execution of the duties of the Ombudsman itself although there are still some constraints that can affect implementation of the duties of the Ombudsman itself as limited human resources, limited budget and the appointment of task binding / writing.Keywords : Implementation , the duties and functions, Ombudsman Representative of Riau ,Ombudsman